Determination of Quality Nursing Follow-up toward Child’s with Burns Injuries in Baghdad City Hospitals - Ali A. Al-Sudani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: To determine of the quality follow-up care provided by nurses for children with burns in burnunits and centers at Baghdad City Hospitals and to identify of the relationship between nurse’s demographiccharacteristics like (gender, age, years of experience, monthly income, place of training sessions, courseof training in burns, level of education) and their follow-up of burns care provided to children with burnsinjuries. Methodology: A descriptive study design has been conducted in burns centers and burns unitsat the Teaching Hospitals in Baghdad City from the January 14th of 2018 up to the 17th of May 2018.Apurposive non probability sample of (70) nurses were selected from burns centers and units . and they haveat least one year of experience in burn centers. The questionnaire is consisted of two parts , the first partis concerning with nurse’s demographic characteristics (7) items, while the second part is dealing withnurses’ practices (follow-up care) and composed of (27) items about nurses’ practices of child’s with burnsat burn centers and units. Select the stability of the questionnaire during and select the pilot study through agroup of 13 experts. Been described and data analyzed through using of 2 statistical approaches: descriptivestatistical analysis and inferential statistical analysis. Results: The study revealed 12;(17.1%) of the samplehas acceptable practices 58; (82.9%) of them has poor practices and good 0;(0.0%) of the sample has goodpractices about follow-up care for child’s with burns at burn centers and units. Moreover, the findings reflectsthat no significant relationship between nurse’s practices and their demographic characteristics. However,significant relationship is found between their practices there is a significant relationship between trainingsessions of education and their practices.